The attitudes and opinions of intensive care nurses on the use of physical restraints - Maleho, Mabona Ednah (My University, 2018)
Background: Despite the uncertainty over the ability of physical restraints to maintain patient safety, as well as the potential for undesirable psychological and physical patient outcomes and ethical concerns, physical restraints use is still common in many ICUs in different countries. Physical restraints are prescribed by the physician but the ICU nurse remains the decision maker responsible in assessing the need, application and removal of physical restraints on patients in the ICU setting. Purpose of the study: The purpose of this study was to describe nurses’ attitudes and opinions on the use of physical restraints in adult ICUs of a tertiary academic hospital in Johannesburg, with the intention to suggest and create awareness to nurse educators on what needs to be included in the curriculum on topic of physical restraints. This may also provide guidance to policy makers on the best practice that need to be considered when implementing a policy in the clinical setting. Method: A descriptive, non-experimental, quantitative survey design was used. Data was collected using an eighteen (18) item questionnaire developed by Freeman, Hallett and McHugh (2015) titled “Attitudes and opinions of ICU nurses on the use of physical restraints’’. The questionnaire was divided into four sections. Convenience sampling was used and a sample size of 113 was used. Descriptive and comparative statistics were used for data analysis. The statistical test used includes Chi-square test and Fisher’s exact test and testing was set at 5% level of significance Results: Most nurses indicated that there is a need for physical restraints use in the ICU setting in order to provide an environment that is safe for the patient. Physical restraints as a management option were preferred over sedation. There was no consensus about the maximum time that an individual patient can be restraint, agitated behaviors such as pulling of endotracheal tubes and medical devices has been noted as the most reason for exceeding the maximum time that an individual patient can be restraint. Nurses were happy to discuss the use of physical restraints with relatives. There was a perceived need for training on use of physical restraints, availing a written policy on physical restraints and support from the medical staff. There was association between ICU nurses’ years of experience, report on availability of written policy on the use of physical restraints, reports on having training on the application of physical restraints and their attitudes and opinions on the use of physical restraints in some statements regarding such. Conclusion: Nurses need support and guidance from other health care workers in cases of using physical restraints. There is need for availability of physical restraints policy to aid nurses’ clinical decision making. Relevance to clinical Practice: There have to be alternative methods and thorough patient assessment of managing agitated patients before implementation of physical restraints, these methods can be pain management and allowing relatives to be at the patient bed side. Key words: Physical restraints, Attitudes, Opinions, Intensive Care, Nurses, Clinical decision making
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg In partial fulfilment of the requirements for the degree of Master of Science in Nursing. Johannesburg, 2018.
Keywords: Intensive Care Units; Restraint, Physical; Nurses; Clinical Decision-Making; Attitude